IMPLIKASI BRAND IMAGE DAN KUALITAS LAYANAN HOTEL TERHADAP KEPUASAN PELANGGAN - Fanny Oryzativa; Niken Febrina Ernungtyas (CHANNEL: Jurnal Komunikasi, 2020)
The purpose of this study is to describe the influence of Brand Image and hotel service quality on customer satisfaction and intentions with four dimensions of service quality that increase the potential for increasing customer satisfaction, employee behavior, room facilities, protection, and food quality. The methodology in this study uses a questionnaire that was adopted and adapted from previous studies. The survey was conducted by issuing questionnaires to 30 Swiss-bel hotel customers which were then analyzed using simple linear regression to discuss Brand Image and service quality on customer satisfaction. The results showed that customer satisfaction and Brand Image produced the greatest influence at 0.920. Get the lowest results from physical evidence and customer satisfaction that only get results of 0.282. This study shows that service quality is important because it can lead to increased customer satisfaction, and it can also help increase motivation for others that can be realized. Hotel operators and decision makers in the hotel sector must get to improve service quality because they have the potential to gain customer satisfaction.